1997
DOI: 10.1002/(sici)1097-0320(19970301)27:3<275::aid-cyto10>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Bax upregulation is an early event in cisplatin-induced apoptosis in human testicular germ-cell tumor cell line NT2, as quantitated by flow cytometry

Abstract: Expression of the apoptosis‐associated proteins Bcl‐2 and Bax was quantitated by flow cytometry (FCM) in chemosensitive testicular germ‐cell tumor NT2 cells, and the results were compared with those obtained by Western blotting. NT2 cells were incubated with cisplatin (3.1 μM for 2 h at 37°C), and 24, 48, and 72 h later were analyzed for induction of apoptosis, and for modulation of the expression of cell death suppressing protein Bcl‐2, as well as cell death promoting protein Bax. Apoptosis was quantitated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
18
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 21 publications
7
18
0
Order By: Relevance
“…[52][53][54] Chemotherapeutic agents also induce cancer cell death through upregulation of Bax. 55) Therefore, our result might be consistent with the report by Wang et al, 56) who had shown that Adv-IκBdN sensitizes chemoresistant tumors to a chemotherapeutic compound, CPT-11. In their report, the inactivation of NF-κB by Adv-IκBdN and the activation of Bax by chemotherapy might have synergistically promoted tumor regression.…”
Section: U251 T-98gsupporting
confidence: 93%
“…[52][53][54] Chemotherapeutic agents also induce cancer cell death through upregulation of Bax. 55) Therefore, our result might be consistent with the report by Wang et al, 56) who had shown that Adv-IκBdN sensitizes chemoresistant tumors to a chemotherapeutic compound, CPT-11. In their report, the inactivation of NF-κB by Adv-IκBdN and the activation of Bax by chemotherapy might have synergistically promoted tumor regression.…”
Section: U251 T-98gsupporting
confidence: 93%
“…Kitada et al (1996) demonstrated that g-radiation applied to radiosensitive cells upregulated expression of the Bax protein and induced apoptosis. The anti-cancer drugs cisplatin, etoposide, and paclitaxel, exert cytotoxicity by triggering the upregulation of Bax (Boersma et al, 1997), and Baxinduced apoptosis (Chresta et al, 1996;Strobel et al, 1996;Wagener et al, 1996). McCurrach et al (1997) showed that ®broblasts obtained from mice in which the Bax gene had been knocked out, were resistant to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the Bcl-2 protein family include the proapoptosis protein Bax-␣ and the antiapotosis proteins Bcl-2 and Bcl-xL (reviewed in references 41 and 6, respectively). Induction of Bax-␣ expression in neurons is associated with apoptosis (4,9,12,31,32,40,63,67). In contrast, induction of Bcl-2 or Bcl-xL expression may prevent neuronal apoptosis induced by various mitochondrial-mediated insults, including NMDA receptor overactivation (2,7,60,68).…”
mentioning
confidence: 99%